Different regulatory mechanisms of the capsule in hypervirulent Klebsiella pneumonia: “direct” wcaJ variation vs. “indirect” rmpA regulation - Wang, Weiwen; Tian, Dongxing; Hu, Dakang; Chen, Wenjie; Zhou, Ying; Jiang, Xiaofei (Frontiers in Cellular and Infection Microbiology, 2023)
Hypervirulent Klebsiella pneumoniae produce an increased amount of capsular substance and are associated with a hypermucoviscous phenotype. Capsule production is regulated by capsular regulatory genes and capsular gene cluster variations. In the present study, we focus on the effect of rmpA and wcaJ on capsule biosynthesis. RmpA as important capsular regulator, its sequences are conversed in different serotypes. RmpA promoted the production of hypercapsules by simultaneously acting on three promoters in cps cluster, indicating the presence of rmpA determines hypercapsule and hypervirulence. Whereas wcaJ, encoding the initiating enzyme of CPS biosynthesis, its loss result in the termination of capsular synthesis. Different from rmpA, wcaJ sequences are different in different serotypes. Moreover, the results verified that K2 wcaJ could form hypercapsule in K2044 strains (K1 serotype), but K64 wcaJ could not. But the switching between K1wcaJ and K2wcaJdid not affect the virulence of the strains in terms of serum resistance, Galleria mellonella larvae infection, and the release of inflammatory factors. In a word, rmpA and wcaJ regulate capsular synthesis and virulence in different directions.